Formula One : the champions : the legendary drivers of F1 - Hamilton, Maurice; Cahier, Bernard; Cahier, Paul-Henri, 1952-; Ecclestone, Bernie, 1930- (London : White Lion Pub., 2021)
"Since the Grand Prix's start in 1950 just thirty-three men have achieved the accolade of Formula One World Champion. For the first time, legendary Formula One commentator Maurice Hamilton and award-winning photographers Bernard and Paul-Henri Cahier bring the heroes of this iconic sport together, in a photographic portrayal of the poise, skill and winning mindset that separates the fast from the furious, the elite from the talented"--Adapted from publisher description.
Keywords: Automobile racing drivers; Automobile racing; Grand Prix racing; Automobile racing drivers; Automobile racing; Grand Prix racing